Sharia Compliance and Gratification Ethics: Analyzing Fatwa 039/DFPA/V/1445 on Gifts from Students and Parents in the School Context - Arifin, Muhammad; Setiawan, Rizal (MUI Sulawesi Selatan, 2024)
This study aims to analyze the Islamic legal perspective on the acceptance of gifts by teachers from students or their parents, as addressed in Fatwa No. 039/DFPA/V/1445 issued by the Dewan Fatwa Perhimpunan Al-Irsyad. The research explores how Islamic values influence the ethical boundaries of professional relationships in educational settings. A normative legal approach is employed, utilizing primary sources from the Qur’an, Hadith, and classical as well as contemporary scholarly opinions. The analysis is framed within the principles of justice (‘adl), trustworthiness (amānah), and educational professionalism. The findings indicate that receiving gifts is legally permissible (mubāḥ) if the gift is given sincerely without coercion, undue influence, or expectations of preferential treatment. Conversely, it becomes prohibited (ḥarām) when the gift is intended to sway the teacher's decisions, causes favoritism, or fosters social inequality due to its value or motive. The study offers original insights by contextualizing a contemporary fatwa within classical jurisprudence and modern educational ethics. Its implications emphasize the importance of maintaining teacher integrity and suggest practical guidelines for educators and parents in aligning gift-giving practices with Islamic ethical standards. This research contributes to the broader discourse on professional ethics and Islamic law in educational institutions.